1996
DOI: 10.1103/physrevlett.76.4074
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Dynamics in Periodically Stimulated Squid Giant Axons

Abstract: Action potentials resulting from periodic stimulation of nerve axons occur at intervals that are irregular at moderate stimulation frequencies. Histograms of the intervals are multimodal, as seen in stochastic resonance. At higher stimulation frequencies, the action potentials are suppressed entirely, leaving only subthreshold dynamics. Return maps constructed from data show that both types of response are governed by the same deterministic one-dimensional description, with an unstable subthreshold fixed point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 21 publications
5
64
0
1
Order By: Relevance
“…The values of the system parameters used in this study are a=0.753617, b=0.745338, and c=3.28076. These values are the same as those used in a prior study that showed the FN model produces responses similar to that of the squid giant axon to rapid pulsatile stimulation (Kaplan et al 1996).…”
Section: Methodssupporting
confidence: 57%
See 3 more Smart Citations
“…The values of the system parameters used in this study are a=0.753617, b=0.745338, and c=3.28076. These values are the same as those used in a prior study that showed the FN model produces responses similar to that of the squid giant axon to rapid pulsatile stimulation (Kaplan et al 1996).…”
Section: Methodssupporting
confidence: 57%
“…A surprising feature of the response of the FN model is that it can be irregular even in the absence of ongoing noise (Ermentrout 1984;Feingold et al 1988;Lakshmanan 1988, 1994;Sato and Doi 1992;Rabinovitch et al 1994;Doi and Sato 1995;Kaplan et al 1996;Rabinovitch and Rogachevskii 1999). Here, we show that completely eliminating ongoing noise improves prominent aspects of the fit to the auditory nerve data.…”
Section: Eliminating Noise Improves Aspects Of the Fn Model's Irregulmentioning
confidence: 99%
See 2 more Smart Citations
“…One such instance has arisen recently that is related to the response of isolated single neurons to trains of repetitive pulsatile stimuli. It is known from several studies that with variation in the period of pulsatile stimulation an alternating pattern of period and chaotic response can be observed in a single excitable neuron [5][6][7][8][9]. In fact it is possible to observe a period adding bifurcation interspersed with windows of chaos.…”
Section: Introductionmentioning
confidence: 91%